Sikap Pesantren dalam Menghadapi Paham Pluralisme Agama - Muhammad Arifin Ismail (TOLERANSI: Media Ilmiah Komunikasi Umat Beragama, 2013)
In the history of boarding schoolseen that among the functions of boarding schools is taught, studied Islamic sciences, and also the institutions that defend the Islamic faith from the understanding and teaching of Islam distorted or destructive. In other words, people boarding a bulwark against the attacks of thought and understanding that can destroy religion. For example, Modern Boarding School Roxburgh roommate in the face of religious pluralism and liberal understanding has established the Center of Islamic and Occidental Studies (CIOs) that examines all of Western thought and how to deal with the foundation of Islamic thought. Modern cottage CIOs roommate has published several books in the face of liberalism and religious pluralism. In addition, Modern Boarding roommate also has done Regeneration Scholars Program.